Historical Evolution of Educational Technologies in Mexico (Docentes 2.0 Journal, 2020)
During the last decades have surged new technologies that have impacted the way education unfolds to better understand better the phenomenon more globally. these technologies continue to emerge day by day.  Therefore, the objective of this research is to do a historical analysis of the progress of such technologies, the above making a projection towards the future; it is worth mentioning that the data was obtained through an analysis of existing information in documentary sources. During the last century, a variety of technologies have been used ranging from the radio, mainly in the 1920s and 1930s; television used primarily in the 1940s to 1960s. In the years 1960 to 1995 the open modality educational system would become popular, made through audiovisual media. Later in the 80's computers would begin to be used for educational purposes; and since 1995 it has been quite common that in educational strategies use the internet, as well as mobile devices. In conclusion that the use of educational technology will continue to evolve constantly, therefore teachers and educational authorities they must be prepared to get the most out of upcoming technologies applied to the educational field.
Keywords: Educative technology; chronological historicity; technological advances